2012
DOI: 10.2165/11596390-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin

Abstract: Despite nearly five decades of clinical use, vancomycin has retained a significant and uncontested niche in the antibacterial arsenal because of its consistent activity against almost all Gram-positive bacteria. Nevertheless, major vancomycin toxicities have been reported in the literature - in particular, nephrotoxicity and ototoxicity. Vancomycin pharmacokinetics have been described in numerous studies for 25 years. This review presents a synthesis of the reported population pharmacokinetic models of vancomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
66
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(72 citation statements)
references
References 41 publications
3
66
2
1
Order By: Relevance
“…In contrast, our model based on peak and trough concentrations was worse at predicting the true AUC from vancomycin trough concentrations. This is an extremely important point, since nearly all of the published vancomycin population models are based on such limited peak-trough sampling, especially in pediatric populations (23). However, it is possible that if two more informative, optimally sampled points after the end of the infusion are selected, then such a model may serve as a better Bayesian prior.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our model based on peak and trough concentrations was worse at predicting the true AUC from vancomycin trough concentrations. This is an extremely important point, since nearly all of the published vancomycin population models are based on such limited peak-trough sampling, especially in pediatric populations (23). However, it is possible that if two more informative, optimally sampled points after the end of the infusion are selected, then such a model may serve as a better Bayesian prior.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the translation of single trough concentration measurements into an integrated concentration-time profile for AUC estimation is achievable but requires parameter assumptions and mathematical modeling (2). These assumptions include a population estimate of a weight-based volume of distribution (V) and clearance (CL), which is based on creatinine clearance (CLcr) (3).…”
mentioning
confidence: 99%
“…Several studies have benchmarked the relationship between vancomycin V and TBW but have also suggested that the vancomycin V estimate per kilogram diminishes with increasing TBW (3)(4)(5). Bauer et al demonstrated that the mean vancomycin V values were 0.32 liters/kg and 0.68 liters/kg in morbidly obese (165 kg) and normal-weight (68 kg) subjects, respectively (4).…”
mentioning
confidence: 99%
“…The pharmacokinetics of vancomycin has shown large interindividual variability, primarily linked to a patient's age, clinical condition, and disease (3,4). Patients in oncology represent a critical population in whom inadequate empirical antibacterial therapy may result in infection-related morbidity and increased mortality.…”
mentioning
confidence: 99%